Budget Implementation Performance Indicators in Dual Institutional Roles: A Case Study of KPPN Yogyakarta as Work Unit and State General Treasurer - Sri Mulyati; Valentina Lurahindria (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
This study aims to analyze the most dominant Budget Implementation Performance Indicators (IKPA) and the factors causing differences in IKPA achievement based on the dual roles of KPPN Yogyakarta as a work unit and the State General Treasurer. This research employs a qualitative approach using interview data and secondary IKPA data from 2022–2025. The findings reveal that DIPA Page III deviation, budget absorption, and output achievement are the most influential indicators affecting overall IKPA performance. Differences in IKPA achievement between the two institutional roles are primarily driven by variations in managerial control, budget management complexity, and the characteristics of supervised work units. These findings indicate that IKPA performance is shaped not only by internal budget management quality but also by institutional role and governance structure. Therefore, efforts to improve IKPA achievement should prioritize strengthening budget planning, monitoring mechanisms, work unit supervision, and optimization of dominant performance indicators